انعقاد نکاح سے متعلق مسائل کی تفہیم میں اہل علم کی رائے:تطبیقی پہلوکاجائزہ: Opinions of scholars in the understanding of problems related to marital conduct: an evaluation of the applied aspect - Dr. Saeed Ur Rahman; Dr. Muhammad Imran Malik; Dr. Sajjad Ahmed (Al Manhal Research Journal, 2023)
Marriage constitutes a significant cornerstone within the context of familial dynamics. During the Jahiliyyah period, the institution of marriage existed in various manifestations. However, it is essential to note that certain prevalent beliefs during this era harmed the sanctity of this sacred union. With the emergence of Islam, Prophet Muhammad (peace be upon him) undertook three significant actions. The user's query seeks an explanation or justification for a particular phenomenon or concept. The individual persisted in reviving the practices and traditions of Hazrat Ibrahim, a significant endeavor with beneficial implications for humanity. The individual in question unequivocally dismissed specific issues that lacked positive attributes. Additionally, due to ignorance, they proceeded to modify the customs, practices, and matters that had become intertwined with polytheism. Nikah, a marital approach, emerged as a custom influenced by the Sunnah of Ibrahim. However, it underwent modifications as time progressed. The Prophet Muhammad (peace be upon him) identified the problems from ignorance. Nevertheless, it is worth noting that a variant of the institution known as Nikah existed in Arab civilization. The topic of marriage is being deliberated upon due to two primary factors. There are two primary reasons for the significance of observing fasting during Ramadan. Firstly, it is mandated as a religious obligation in the Qur'an. Secondly, it holds considerable importance in response to societal requirements. However, due to novel challenges and cultural practices, a significant concern pertains to the practical implementation of the commandments outlined in the Qur'an within societal contexts. Difficulty can also arise as a result of habituation. The subsequent discussion pertains to the identical subject matter.